Examining Academics’ Strategies for Coping With Stress and Emotions: A Review of Research - Salimzadeh, Raheleh; Hall, Nathan C.; Saroyan, Alenoush (Frontiers in Education, 2021)
Existing research suggests that numerous aspects of the modern academic career are stressful and trigger emotional responses, with evidence further showing job-related stress and emotions to impact well-being and productivity of post-secondary faculty (i.e., university or college research and teaching staff). The current paper provides a comprehensive and descriptive review of the empirical research on coping and emotion regulation strategies among faculty members, identifies adaptive stress management and emotion regulation strategies for coping with emotional demands of the academic profession, synthesizes findings on the association between such strategies and faculty well-being, and provides directions for future research on this topic.